Capitalism when Labor was Capital: Slavery, Power, and Price in Antebellum America - Rosenthal, Caitlin (Capitalism: A Journal of History and Economics, 2020)
, Abstract:, The new historians of capitalism have been reluctant to define “capitalism,” warning that a narrow definition could artificially constrain our analysis of the system on the ground. But, as the field matures, thinking more about what capitalism is can help both to clarify cross-disciplinary debates and also to offer a deeper theoretical understanding of the relationship between slavery and capitalism. This paper unfolds in two parts. First, I explore the problem of defining of capitalism, offering one possibility based on the commoditization of labor as it results from the distribution of capital. Such a definition attempts to reconcile understandings of capitalism that focus on wage labor with the circumstances of slavery. The second half of the article considers late antebellum American slavery through the lens of this proposed definition, asking to what extent enslaved people and their labor were “commoditized.” To do this, I explore four genres of valuation in which slaveholders graded and priced enslaved people: inventories, the system of fractional hands, price circulars, and finally, negotiations over manumission. Planters’ calculations reflect their efforts to understand the infinite variety of enslaved lives as abstract, measurable units of human capital. They enjoyed the power to shift among different modes of valuation to answer different questions, and when it served their interests they abandoned the language of commoditization altogether.
Keywords: Business History and race